Kin in the game: How family ties help firms overcome campaign finance regulation - Pablo Balán; Juan Dodyk; Ignacio Puente (University of Chicago Booth School of Business, Stigler Center for the Study of the Economy and the State, 2023)
Can campaign finance regulation curb the political influence of economic actors? In this article, we identify a new factor that may hinder its effectiveness-the social structure of organizations. We argue that such regulation creates cooperation dilemmas in firms' leadership and propose that a specific feature of organizations-family ties-help solve such problems. We evaluate this argument by studying a Supreme Court ban on corporate contributions in Brazil. Using a difference-in-differences design and data on family ties in Brazilian public companies, we show that, following the ban, members of firms' controlling families substitute individual for corporate contributions. Furthermore, we document the presence of peer effects in the contribution behavior of family members, suggesting that family ties transmit influence. These bifurcated effects illustrate how organizational structure can be a source of de facto power by limiting the effectiveness of programmatic reforms, and thus contain a cautionary tale for policymakers.
Keywords: 330